Essential oils in food processing chemistry, safety and applications - Hashemi, Seyed Mohammad Bagher 1986- (IFT Press Series, 2018)
A guide to the use of essential oils in food, including information on their composition, extraction methods, and their antioxidant and antimicrobial applications. Consumers’ food preferences are moving away from synthetic additives and preservatives and there is an increase demand for convenient packaged foods with long shelf lives. The use of essential oils fills the need for more natural preservativesto extend the shelf-life and maintaining the safety of foods. Essential Oils in Food Processing offers researchers in food science a guide to the chemistry, safety and applications of these easily accessible and eco-friendly substances. The text offers a review of essential oils components, history, source and their application in foods and explores common and new extraction methods of essential oils from herbs and spices. The authors show how to determine the chemical composition of essential oils as well as an explanation of the antimicrobial and antioxidant activity of these oils in foods. This resource also delves into the effect of essential oils on food flavor and explores the interaction of essential oils and food components.--Provided by publisher.